Malignant fibrous histiocytoma of sternum: an unusual cause of pyrexia of undetermined origin. Issue 770 (December 1989) - Grieco, A.; Caputo, S.; Silvestri, E.; Caradonna, P.; Bertoli, A.; Greco, A. V.
Abstract : Malignant fibrous histiocytoma of the bone is a very rare tumour mainly affecting long bones, and the most common presenting symptom is local pain. A case of malignant fibrous histiocytoma presenting with pyrexia of undetermined origin and arising in the sternum, a localization not previously described, is reported. The patient died with septic shock after multi-drug chemotherapy including high dose methotrexate treatment with citrovorum factor rescue.